Distribution, phenology and host plants of Danish bees (Hymenoptera, Apoidea) - Rasmussen, Claus; Schmidt, Hans Thomsen; Madsen, Henning Bang (Zootaxa, 2016)
Based on the examination of 47.629 specimens of bees from Denmark (54.6ºN to 57.8ºN) we summarize for the first time the distribution, phenology and host-plants for all 286 known species occurring in the country. The mapped occurrence records distinguish whether species are found only in 1974 or earlier, 1975 or later, or in both periods. Danish bees are recorded active from February 29 through October 21 and have been collected in 79% of the 10x10 km Universal Transverse Mercator (UTM) squares covering the country; seven UTM squares have over 100 reported species. Some UTM squares are poorly sampled, including less than five species recorded from 31% of the sampled squares. In addition bees are recorded from 282 different plants representing 50 families with the majority of observations from Asteraceae and Fabaceae (Leguminosae). The data, compiled from all major bee collections in the country, will provide policy makers and scientists a tool for establishing strategies for pollinator conservation and further research.